Lixiviación de proteínas en alimento balanceado para camarón blanco (litopenaeus vannamei) a diferentes salinidades. - Chamba Ponce, Kevin Bryan (Machala : Universidad Técnica de Machala, 2022)
White shrimp production depends on water quality as well as the balanced diet provided. These foods suffer a loss of protein, called leaching, in such a way that it will bring with it negative consequences in production. The objective of this work was to evaluate the combined and individual effect of salinity and immersion time on protein leaching of a commercial balanced feed for Litopenaeus vannamei. A completely random factorial experiment divided into 3x4 was carried out, with three salinity concentrations (0‰, 15‰, 30‰), 4 immersion times (30 min, 60 min, 120 min, 360 min), where 4 g of balanced feed of 32% protein in each experimental unit taken to 1 liter of water of different salinities and times, thus forming 12 combinations of treatments, which were replicated 3 times, in a homogeneous experimental environment, to then obtain the percentage of protein content in the pellet by the Kjeldahl method. The results showed that individually at a salinity of 30 ppt, greater leaching occurs with 27.36% protein (14.5% leached) than in fresh water with 31.17% protein (2.60% leached). Regarding the immersion time in water at 30 ppt, at 30, 60 and 120 minutes there was an average leaching of 15.8%, then at 360 min there was leaching of 10.3%, speculating that it is due to the decomposition of bacteria present in the water. balanced feed samples. As there were no interaction effects between each study factor, the best combined effect was evaluated, being 30 ppt at 60 minutes the combination with the highest leaching, having 26.83% protein (16.15% leached), while 0 ppt at 30 min contained 31.98% protein (0.063 percent leached). Concluding that salinity influences protein loss without negative consequences since this loss works as an attractant to the organism. Regarding the immersion time, it was shown that there is almost the same losing 15.8%. On the other hand, in terms of salinity-time, it was shown that less protein is leached in low-salinity water.
La producción de camarón blanco depende de la calidad de agua al igual que la dieta balanceada proporcionada. Estos alimentos sufren una pérdida de proteínas, llamada lixiviación, de manera que traerá consigo consecuencias negativas en la producción. El objetivo de este trabajo fue evaluar el efecto de manera combinada e individual de la salinidad y tiempo de inmersión en la lixiviación de proteínas de un alimento balanceado comercial para Litopenaeus vannamei. Se realizó un experimento factorial completamente al azar fraccionado en 3x4, con tres concentraciones de salinidad (0‰, 15‰, 30‰), 4 tiempos de inmersión (30 min, 60 min, 120 min, 360 min), donde se sumergió 4 gr de alimento balanceado de 32% proteína en cada unidad experimental llevada a 1 lt de agua de las diferentes salinidades y tiempos, formando así 12 combinaciones de tratamientos, mismos que se replicaron 3 veces, en un entorno experimental homogéneo, para luego obtener el porcentaje de contenido de proteína en el pellet mediante el método Kjeldahl. Los resultados demostraron que individualmente a una salinidad de 30 ppt ocurre mayor lixiviación con 27,36 % de proteína (14,5% lixiviado) que en agua dulce con 31,17% de proteína (2,60% lixiviado). En cuanto al tiempo de inmersión en agua a 30 ppt a los 30, 60 y 120 minutos hubo lixiviación promedio de 15,8%, luego a los 360 min hubo lixiviación de 10,3% especulando que se debe por descomposición bacteriana presente en las muestras de alimento balanceado. Al no presentar efectos de interacción entre cada factor de estudio se evaluó el mejor efecto combinado siendo 30 ppt a 60 minutos la combinación con mayor lixiviación, teniendo 26,83% de proteína (16,15% lixiviado), mientras que 0 ppt a 30 min contuvo 31,98% de proteína (0,063 porcentaje lixiviado). Concluyendo que la salinidad influye en la pérdida de proteínas sin consecuencias negativas ya que funciona esta pérdida como atractante al organismo. En cuanto al tiempo de inmersión, se demostró que existe casi igual al perder 15,8%. Por otra parte, en cuanto a salinidad-tiempo se demostró que en agua de baja salinidad se lixivia menos proteína.
Keywords: LIXIVIACION; PROTEINA; SALINIDAD; CAMARON; TIEMPO INMERSION